Female genital schistosomiasis burden and risk factors in two endemic areas in Malawi nested in the Morbidity Operational Research for Bilharziasis Implementation Decisions (MORBID) cross-sectional study. - Olimpia Lamberti; Sekeleghe Kayuni; Dingase Kumwenda; Bagrey Ngwira; Varsha Singh; Veena Moktali; Neerav Dhanani; Els Wessels; Lisette Van Lieshout; Fiona M Fleming; Themba Mzilahowa; Amaya L Bustinduy (PLoS Neglected Tropical Diseases)
Background Female genital schistosomiasis (FGS), caused by the parasite Schistosoma haematobium (Sh), is prevalent in Sub-Saharan Africa. FGS is associated with sexual dysfunction and reproductive morbidity, and increased prevalence of HIV and cervical precancerous lesions. Lack of approved guidelines for FGS screening and diagnosis hinder accurate disease burden estimation. This study evaluated FGS burden in two Sh-endemic areas in Southern Malawi by visual and molecular diagnostic methods. Methodology/principal findings Women aged 15-65, sexually active, not menstruating, or pregnant, were enrolled from the MORBID study. A midwife completed a questionnaire, obtained cervicovaginal swab and lavage, and assessed FGS-associated genital lesions using hand-held colposcopy. 'Visual-FGS' was defined as specific genital lesions. 'Molecular-FGS' was defined as Sh DNA detected by real-time PCR from swabs. Microscopy detected urinary Sh egg-patent infection. In total, 950 women completed the questionnaire (median age 27, [IQR] 20-38). Visual-and molecular-FGS prevalence were 26·9% (260/967) and 8·2% (78/942), respectively. 6·5% of women with available genital and urinary samples (38/584) had egg-patent Sh infection. There was a positive significant association between molecular- and visual-FGS (AOR = 2·9, 95%CI 1·7-5·0). 'Molecular-FGS' was associated with egg-patent Sh infection (AOR = 7·5, 95% CI 3·27-17·2). Some villages had high 'molecular-FGS' prevalence, despite <10% prevalence of urinary Sh among school-age children. Conclusions/significance Southern Malawi carries an under-recognized FGS burden. FGS was detectable in villages not eligible for schistosomiasis control strategies, potentially leaving girls and women untreated under current WHO guidelines. Validated field-deployable methods could be considered for new control strategies.